GRAMMATICAL ERROR ANALYSIS OF STUDENT’S COMMENT WRITING BASED ON FACEBOOK GAME IN ENGLISH INTENSIVE CLASS OF STAIN JURAI SIWO METRO 2013 - Dedy Subandowo (State Institute for Islamic Studies IAIN of Metro, 2014)
This paper is titled “Grammatical Error Analysis of Students’ Comment Writing Based on Facebook Game in English Intensive Class of STAIN JURAI SIWO METRO 2013”. The aim of this research is to describe grammatical errors which are made by the students of English Intensive Class. It is a qualitative-descriptive research. The data are taken from the result of students‟ comment writing on Facebook game in English intensive class. Meanwhile, the techniques to collect the data used note and observation. The result is displayed in words. The research shows that the grammatical errors made by the students in English intensive class are using double auxiliary, confusing to apply nominal or verbal sentence, and making error interrogative form pattern.